Kontext und Bedeutung - Ibaňez, Robert (Studia Germanica Posnaniensia, 2018)
Starting from the concept of text as "a grammatically coherent component of the act of utterance" the author takes a critical view of the up-to-date understanding of the text meaning, differentiating it with respect to a given communicative situation as that of the sender and that of the recipient, i.e. in the way it is required by so called radical constructivism. Contextual meaning with language interactions is constituted by the individual and social context of the communicators. Following the tradition of Malinowski the author distinguishes within the cultural context between a conventional and connotative one, emphasizing also such factors as the knowledge of the world and the individually experienced context. All kinds of context are shown in their mutual relations as well as to the text meaning.